Bahtsul Masail dan Problematikanya di Kalangan Masyarakat Muslim Tradisional - Ahmad Munjin Nasih (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
Up to now, Nahdlatul Ulama always presents issues for discussion and analysis. Among others is Bahstul Masail forum which is designed to find solution for religious issues. The forum is an interested object of study for to aspects. The first is about the process of drafting a fatwa (non-binding legal opinion) to a given religious issue and the discussion precedes it. The second aspect concerns disseminating and communicating a fatwa to Nahdlatul Ulama members, especially the person who inquire the issue.